Impact of Surgeon Experience in the Resection of Basal Cell Carcinoma of the Head and Neck Region - Carlos Gonzalo Acosta Mayorga; Piedad Elizabeth Acurio Padilla; Guido Nino Guida Acevedo (Revista Finlay)
Foundation: surgical excision with adequate margins is considered the standard treatment for cutaneous basal cell carcinoma, due to its association with lower rates of recurrence and postoperative metastasis. Objective: to evaluate the impact of surgical experience in a high-volume head and neck surgery department in relation to margin status in basal cell carcinoma resection. Methods: a retrospective and correlational descriptive study was carried out on 412 patients selected from those undergoing surgical treatment for basal cell carcinoma in the head and neck region in the department that treats this condition between 2018 and 2022. Quantitative variables were established to characterize the demographic composition of the sample and the values of the resections. The data were analyzed with the Statistica software package. Chi-square, Fisher, and Mann-Whitney tests were used to determine statistical significance. The results were considered significant for p value less than 0.05. The results were presented in quantities and percentages. Given its retrospective nature, the study did not require approval from the University Bioethics Committee. Results: the study included 245 men and 167 women. Most of the tumors were located in the nose and pinna. The most common histological subtype was nodular. Tumor size was up to 20 mm in 354 cases. Positive surgical margins were observed in 92 cases. No significant differences were found in terms of performing positive surgical margins between residents and specialists. Conclusions: the results of the present study demonstrate that adequate surgical training in a specialized head and neck surgery service is a determining factor in achieving free surgical margins in basal cell carcinoma of the head and neck region.